A curricular model to train doctoral students in interdisciplinary research at the food-energy-water nexus - Murray, Rianna Teresa; Marbach-Ad, Gili; McKee, Kelsey; Lansing, Stephanie; Winner, Megan Elizabeth; Sapkota, Amy Rebecca (Frontiers in Education, 2023)
Food, energy and water (FEW) systems are inextricably linked, and thus, solutions to FEW nexus challenges, including water and food insecurity, require an interconnected science and policy approach framed in systems thinking. To drive these solutions, we developed an interdisciplinary, experiential graduate education program focused on innovations at the FEW nexus. As part of our program, PhD students complete a two-course sequence: 1) an experiential introduction to innovations at the FEW nexus; and 2) a data practicum. The two courses are linked through an interdisciplinary FEW systems research project that begins during the first course and is completed at the end of the second course. Project deliverables include research manuscripts, grant proposals, policy memos, and outreach materials. Topics addressed in these projects include building electrification to reduce reliance on fossil fuels for heating, agrivoltaic farming to combat FEW vulnerabilities in the southwestern US, assessment of food choices to influence sustainable dining practices, and understanding the complexities of FEW nexus research and training at the university level. Evaluation data were generated from our first three student cohorts (n=33 students) using a mixed method, multi-informant evaluation approach, including the administration of an adapted version of a validated pre-post-survey to collect baseline and end-of-semester data. The survey assessed student confidence in the following example areas: communication, collaboration, and interdisciplinary research skills. Overall, students reported confidence growth in utilizing interdisciplinary research methods (e.g., synthesize the approaches and tools from multiple disciplines to evaluate and address a research problem), collaborating with range of professionals and communicating their research results to diverse audience. The growth in confidence in the surveyed areas aligned with the learning objectives for the two-course sequence, and the interdisciplinary project experience was continually improved based on student feedback. This two-course sequence represents one successful approach for educators to rethink the traditional siloed approach of training doctoral students working at the FEW nexus.